IMPACT OF CHRISTIANITY ON THE AOS OF NAGALAND: INTROSPECTION AND REFLECTION - AO, A Bendangyabang (Journal of Dharma, 2001)
This writing covers the history Of social and cultural transformation of the Aos during the 19"’ and 20th centuries. wili trace how the transformation from Ao Naga traditional life-style and religion to Christianity evolved and influenced the modernization of the tribe. It will evaluate the consequences and enumerate both its meiits and dements. It is a compact history of more than 130 years and an attempt is made to articulate major issues and analyze them.